Robo falcon: an RC robotic bird - Muhammad, Imran (050483); 2009 (Department of Mechatronics (Air University Main Campus) Islamabad., 2009)
Robo Falcon is a radio controlled ornithopter that flies just like a real bird by flapping its wings. Unlike conventional flying machines that use engine or rotor power to produce lift, it uses its wings to fly. Its main power sources are batteries that run a DC motor. Rotary motion of the motor is converted into flapping motion of the wing with the help of certain mechanism, consisting of gear train. For the direction control a rudder has been used mounted on the tail. By steering the rudder left or right the direction of the ornithopter can be controlled. A set of two channel radio transmitter & receiver has been used for radio control purpose. Receiver is mounted on board dedicating one channel for motor drive and the other for rudder control. The whole project revolves around the aerodynamics of a biological bird, as the ornithopter would be the replica of a real bird. Basic aerodynamic forces involved are lift, drag and thrust.
BEMTS